(The Effect of Type of Container and Storage on the Change of pH and Heavy Metal Migration on Moni Juice (Morinda Citrifolia L.) - H Guring Pohan (Warta Industri Hasil Pertanian, 2003)
A study on the effect of type of container and storage time of nony liquid has been conducted.the research were the type of plastic and storage time. the observation done were pH and heavy metal such as: PB,Cu,Fe,Co, the result shows there was no significant effect on the chage of pH and metal migration the contains of Cu between; 0,20-1,22 ppm for plastic drum and 0,25-077 ppm for plastic bottle and fe between :2,20-3,48 ppm for plastic drum the change of pH between 3,73-4,62 for plastic drum and 3,74-4,64 for plastic bottle during storage on nony liquid .